ASKED – the Anglo-Saxon Kent Electronic Database. (15th February 2012) - Harrington, Sue; Brookes, Stuart
The dataset covers the burial records from excavation of 3500 people and their associated artefacts from 120 cemetery sites in Kent, southern England, from the period AD 400–700. It was assembled to facilitate the respective PhD research programmes of the authors, using published, unpublished and grey literature sources. It was made publicly available in 2008 via the Archaeology Data Service as a Special Collection and has had regular downloads thereafter by students, academics and international colleagues. The intention is to expand the dataset nationally, with the next upload to take place in 2012 to cover southern England.